Between private and public law : The contribution of late medieval ius commune to the conceptualisation of diplomatic representation - Dante Fedele (Clio@Themis)
This paper examines the development, by late medieval ius commune jurists, of a notion of diplomatic representation which is rooted in the doctrine of private law agency. In particular, it endeavours to study the basis and limits of ambassadors’ negotiating powers, by analysing some issues relating to procuration and the ratification of treaties. The conclusion illustrates the persistence of the central role of this notion of diplomatic representation in the discussion of the matter right up until the late eighteenth century, thus allowing us to appreciate the importance of the contribution made by late medieval ius commune to the early modern discussion of the status of the ambassador.